Os efeitos da adoção do processo eletrônico na Anatel sob a ótica dos custos de transação - Romaro, Ubirajara Costabile (2019)
The advance of the information technology systems of the mid 1990s promoted a revolution in the way public services were served to citizens, which allowed the use of computerized systems already in the creation of Anatel in 1997. With the increase in the Internet access speed and the resources for storing large volumes of information, in 2015, the National Electronic Process (PEN) and the Electronic Information System (SEI) were implemented in the Federal Public Administration, due to the publication of the Decree No. 8539/15. SEI, responsible for the registration, control, storage and flow of distribution of citizens' requests, replaced SICAP (Integrated System for Control and Monitoring of Processes), which had been introduced in 1997. The citizen's request is understood as his transaction with to Anatel. This research presents the effects for Anatel of the implementation of SEI in place of SICAP, from the perspective of the Transaction Costs Theory.